GRAPHIC NARRATIVES AS COUNTERCULTURE IN MALIK SAJAD’S MUNNU: A BOY FROM KASHMIR - Gulbahar Shah (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper traces the evolution of comics as a countercultural form of resistance and explores how the medium has historically challenged dominant sociopolitical narratives, particularly in the context of American underground comics of the 1960s and their influence on contemporary graphic storytelling. It posits that graphic narratives, derided as ephemeral or childish, continue to be shaky witnesses to the testimony and traumas of history. Through a close reading of Munnu: A Boy from Kashmir by Malik Sajad, the paper illustrates how the legacy of underground comix continues in contemporary South Asian graphic narratives, particularly those emerging from conflict zones. Sajad’s work marries autobiographical memory and political commentary with formal experimentation, including anthropomorphic figuration and fragmented visual layouts, representing the lived experiences of consciousness of ineffable phenomena: locationality and the implications of a body in relation to history. By embedding the personal within the political, Sajad reclaims the narrative from statist and separatist appropriations, producing a subversive visual archive that exemplifies the enduring potential of graphic narratives to unsettle hegemonic truths and foreground alternative epistemologies.